Role of Features and Second-order Spatial Relations in Face Discrimination, Face Recognition, and Individual Face Skills: Behavioral and Functional Magnetic Resonance Imaging Data - Rotshtein, Pia; Geng, Joy J; Driver, Jon; Dolan, Raymond J (Journal of cognitive neuroscience, 2007)
We compared the contribution of featural information and second-order spatial relations (spacing between features) in face processing. A fully factorial design has the same or different “features” (eyes, mouth, and nose) across two successive displays, whereas, orthogonally, the second-order spatial relations between those features were the same or different. The range of such changes matched the possibilities within the population of natural face images. Behaviorally, we found that judging whether two successive faces depicted the same person was dominated by features, although second-order spatial relations also contributed. This influence of spatial relations correlated, for individual subjects, with their skill at recognition of faces (as famous, or as previously exposed) in separate behavioral tests. Using the same repetition design in functional magnetic resonance imaging, we found feature-dependent effects in the lateral occipital and right fusiform regions. In addition, there were spatial relation effects in the bilateral inferior occipital gyrus and right fusiform that correlated with individual differences in (separately measured) behavioral sensitivity to those changes. The results suggest that featural and second-order spatial relation aspects of faces make distinct contributions to behavioral discrimination and recognition, with features contributing most to face discrimination and second-order spatial relational aspects correlating best with recognition skills. Distinct neural responses to these aspects were found with functional magnetic resonance imaging, particularly when individual skills were taken into account for the impact of second-order spatial relations.